Analytical study of oil price fluctuations on the financial balance of the Algerian National Pension fund - chehboub, amina (Journal of Research in Finance and Accounting, 2022)
This research paper came with the aim of the analytical study of oil price fluctuations on the financial balance of the Algerian National pension fund , this is due to the increasing importance that the Algerian state attaches to the social security sector , especially the national pension fund, in view of the importance of oil revenues, in financing the sector through the state’s establishment of the national fund for retirement reserves, whose incole is 3% .dependent on Algerian oil tax revenues. Based on the descriptive approach and using the analytical method. We have given a picture of the status of the national pension fund. In addition to following the path of the oil industry in algeria in recent years. the study reached a set of results, the most important of which is that the most important of which is that the national pension fund experienced a deficit in its financial balance. Which was caused by a number of reasons , on top of which the fund relied heavily on subscriptions for financing. The collapse of oil prices had a negative impact on the financial balance of the fund, its is considered one of the means of state intervention in financing the pension system. In light of the results.